Akibat Hukum Terhadap Surat Keterangan Warisan Yang Dibuat Tanpa Melibatkan Seluruh Ahli Waris Dan Tidak Berdasarkan Surat Wasiat (Studi Tentang Surat Wasiat Nyi Moertinem alias Wiryodiharjo) - Nixon Shadda Priyantonojati; Abdul Jamil (Fakultas Hukum Universitas Islam Indonesia, 2023)
Inheritance law is a norm governing the transfer of assets of a deceased person to the rightful person. There are problems related to the certificate of inheritance which was made privately by not involving all the heirs in the presence of a will that occurred in the case of the heirs of the late Nyi Murtinem. So that two formulations of the problem can be formulated. First, what are the legal consequences of making a certificate of inheritance without involving all heirs and not based on a will from Nyi. Murtinem Second, what are the legal remedies that can be taken by the heirs of the late Mr. Paldjono and the late Mr. Partono against the certificate of inheritance made without involving all heirs and not based on a will from Nyi. Murtinem? The research method in this research is juridical-empirical legal research. Field research examines legal provisions in people's lives. The results of this research are, First, the legal consequences of this problem result in legal defects because formally it contradicts Article 111 paragraph (1) letter c of the Minister of Agrarian and Spatial Planning Regulation Number 16 of 2021 and materially contradicts Article 263 of the Indonesian Book of Laws Criminal. There are 4 legal remedies that can be taken by the heirs of the late Mr Partono and Mr Paldjono, namely mediation, legal action, filing a lawsuit, and requesting mediation.